Wireless Media Access Control: An Overview - Arpit Namdev (AG Volumes, 2023)
Improving wireless network and communication performance relies heavily on well-designed "medium access control" (MAC) protocols. In order for numerous stations to use the same medium, the MAC layer provides a channel access mechanism. Throughput, latency, power consumption, fairness, dependability, and network density are only few of design criteria that must be met by a MAC protocol for various wireless networks. Massive MIMO and "power domain non-orthogonal multiple access" (PD-NOMA) are two multiplexing techniques we suggested for use in contemporary wireless networks. “Massive Multiple-Input Multiple-Output” (MIMO) is the first research strategy that employs a large number of the antenna components to improve the spectral efficiency and power efficiency. The second technique of study (PD-NOMA) allocates a variable amount of power to each station, allowing numerous non-orthogonal signals to part the same set of orthogonal resources. When compared to orthogonal multiple access techniques, PD-NOMA provides superior spectrum efficiency. This study's primary contribution is its demonstration of how enhanced MAC design with optimum functionality may boost wireless networks' spectrum and energy efficiency.